Use Of Fiber Midrib Tree Of Bananas As The Material Alternatives In The Making Brake Drum Motorcycles (NonAsbestos) - Prayoga A (International Conference on Engineering and Technology Development (ICETD), 2017)
brake lining is an important component in a motor vehicle as security aspects memeperlambat drive that serves as the vehicle speed when the driver drove at speeds tinggi.Peneliti will conduct testing using the stem of banana tree fiber materials instead of making materials that use asbestos brake linings, mixed with other filler materials in accordance with the predetermined composition is grafhite, barite, brass, calcium carbonate, and epoxy resin. Manufacture of brake linings made by mixing all the ingredients that have been determined evenly which further pressed with a load of 1 ton for 30 minutes, then the ovenwith a temperature of C for 10 minutes. After the specimen so then tested friction with a load of 2 kg for 3 minutes, so that the obtained level keasusan canvass and a brake lining wear time. Once done then it can test the results of testing dilakukan.Bahwa brake with the stem of a banana tree fiber use feasible inuse because it has a wear rate of 2.05 x grams/detik. which is approximatelythe brake lining wear-owned manufacturer that is 1.64 x grams / .detik